Single non-pharmacological intervention of depression in the elderly with cognitive dysfunction: a systematic review and network meta-analysis - Tan, Zhengyi; Li, Baiyun; Su, Lanxin; Liu, Lihua; Chuang, Yao-Chen (Frontiers in Psychiatry, 2025)
PurposeThis study was conducted to appraise the comparative efficacy of single non-pharmacological methods on depression for cognitive dysfunction patients utilizing network meta-analysis (NMA) and resolve ambiguities in existing literature to help practitioners accurately determine the efficacy and formulate the optimal therapeutic models.DesignSystematic Review and Network meta-analysis.MethodsPubMed, Embase, Cochrane, and Web of Science were searched. The Cochrane Handbook for Systematic Reviews of Interventions was used to assess the risk of bias in the included studies. Two investigators independently undertook data extraction and quality evaluation.ResultOverall, 26 articles incorporating 10 single non-pharmacological interventions were identified. Compared to control, GAME (SMD = −1.00, 95% CrI = −1.70 to −0.39) and mindfulness (SMD = −0.58, 95% CrI = −0.99 to −0.17) significantly alleviated depressive symptoms. RTBC (SMD = −0.49, 95% CrI = −0.88 to −0.09) and MUSIC (SMD = −0.47, 95% CrI = −0.84 to −0.08) showed moderate effects, and PE (SMD = −0.37, 95% CrI = −0.67 to −0.09) showed small effects.ConclusionIn this network meta-analysis, we synthesized 26 trials to quantify the isolated impact of 10 single non-pharmacological interventions on depressive symptoms. Against usual care (basic medical support, sham stimulation, or wait-list), GAME and mindfulness produced the largest and statistically credible reductions. Reminiscence-therapy-based care (RTBC) and music therapy (MUSIC) generated medium benefits, whereas physical exercise (PE) yielded a small yet significant effect. These findings were robust across both direct and indirect evidence, underscoring GAME and mindfulness as the most effective stand-alone non-pharmacological options for mitigating depression.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024517077.